Pengaruh Kesehatan Mental Terhadap Hasil Belajar Mata Pelajaran Pendidikan Agama Islam Di SMK Negeri 1 Bukittinggi - Lara Setiawati; Dodi Pasila Putra; Alfi Rahmi; Hidayani Syam (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
The purpose of this study was to determine the Great Appreciation of the Influence of Mental Health on Learning Outcomes of Islamic Religious Education Subjects at SMK Negeri 1 Bukittinggi. The type of research that researchers conducted was correlation research with a quantitative approach, using a computer package (SPSS). The data used is in the form of numbers distributed to 65 respondents. The data analysis technique used is to do a Validity Test, Reliability Test, Normality Test, Linearity, Simple Linear Regression Test, F Test, and Determinant Correlation Test (R2). Based on the results of data processing, a simple linear regression calculation is obtained with the equation, namely Y = 12.584 + 0.188 X. Based on the equation above, it can be concluded that if mental health increases by one unit, it will affect the learning outcomes of Islamic religious education by 0.188. But if there are no these variables, the value of Islamic religious education learning outcomes is 12.584. The results of the F test obtained for Ftable were 3.99, because Fcount > Ftable (4.355 > 3.99) and a significant value < 0.05 (0.000 < 0.05), so it can be interpreted that mental health has a significant effect on learning outcomes in Islamic religious education. Then Ha is rejected Ho is rejected. The test results above show that mental health has a significant effect on the learning outcomes of Islamic religious education.